On the role of xylan in the final bleaching of Eucalyptus Globulus Kraft pulps - Loureiro, Pedro Emanuel Garcia (2012)
ABSTRACT Brightness stability is a very important property of beached cellulosic pulps. The impact of the final bleaching stage is assessed in this study for the purpose of understanding the fundamental reasons behind the improved brightness stability of bleached eucalypt pulp when the conventional chlorine dioxide stage (D) is replaced by an alkaline hydrogen peroxide stage (P). Particular emphasis was devoted to the role of xylan because within the fibrous structure this component has higher accessibility to brightening agents. Isolated xylans from partially (DED) and fully (DEDD/DEDP) bleached eucalypt kraft pulps were characterized using 1H NMR, UV-Vis in cadoxen solutions, size exclusion chromatography and UV-Resonance Raman spectroscopy @ 325 nm. Comparative analysis was done for xylan isolated from partially bleached pulp (DED) and subjected to treatment either with chlorine dioxide or alkaline hydrogen peroxide under the same final bleaching conditions. Chlorine dioxide final stage induced new unsaturated moieties in xylan structure, while hydrogen peroxide was very effective in the removal of xylan-related chromophores. The role of xylan to the delay of brightness development in the final chlorine dioxide stage was highlighted. UV-vis Diffuse Reflectance and UV Resonance Raman micro-spectroscopy were employed to evaluate the differences on chromophores formation/degradation in fully bleached eucalypt kraft pulp upon both final bleaching stages. Spectroscopic data were coupled to wet chemistry and mass spectrometry analyses of degradation products arisen during hydrothermal ageing of bleached pulps. The complementary analyses have revealed the important role of partially oxidized carbohydrates and of the residual lignin structurally associated to xylan in ageing reactions. A part of the new formed chromophores was the result of iron complexes with ageing products. The leaching of degradation products from pulp in the alkaline peroxide stage was suggested to be a crucial factor that predetermined its lower brightness reversion over the pulp bleached under the weakly acidic chlorine dioxide stage.